Bauhinia orbiculata (Cercidoideae, Leguminosae), a new species from Chapada Diamantina, Bahia, Brazil - Dos Santos, Antonio C.b.; de Queiroz, Luciano P.; Da Silva, Maria A.p.; Paula, Antonio P.o.; Feitoza, Lidiane De L.; de Carvalho, Reginaldo (Phytotaxa, 2023)
Bauhinia orbiculata is a new species of Leguminosae found in the northern portion of the Chapada Diamantina mountain range in the state of Bahia, northeastern Brazil. It occurs in the seasonally dry shrubby vegetation locally known as ‘carrasco’, and is characterized by entire unifoliolate leaves with nine primary veins, rounded to obtuse apex and cordate base, dark ferruginous lower leaf surface, and linear and smooth floral buds. A detailed description, distribution map and illustrations are provided and its relationship with other eastern Brazilian species with entire leaves is discussed.